Gold recovery from precious metals in acidic media by using human hair waste as a new pretreatment-free green material. Issue 1 (February 2021) - Yu, Dan; Morisada, Shintaro; Kawakita, Hidetaka; Sakaguchi, Koichi; Osada, Satoshi; Ohto, Keisuke; Inoue, Katsutoshi; Song, Xi-Ming; Zhang, Guolin; Sathuluri, Ramachandra Rao
Graphical abstract: Highlights: Untreated cut human hair waste was investigated on recovery of precious metals. Human hair waste exhibited high selectivity for Au with reduction and high capacity. Cysteine and cystine in human hair played a key role of Au adsorption and reduction. Stepwise recovery of pure metallic Au from other precious metals was achieved. Stable and abundant hair waste can be an excellent bio-adsorbent for Au recovery. Abstract: We herein propose an advanced gold recovery process employing biomass waste of human origin. Au(III) adsorption on human hair (HH) was found to be efficient and to concurrently reduce Au(III) to metallic gold. The maximum loading capacities of gold on HH and white HH were determined using Langmuir equation fitting to be 3.04 and 3.24 mmol g −1, respectively. This result indicates that melanin pigment in HH is not involved in Au(III) adsorption. The concurrent reduction of Au(III) was confirmed using X-ray diffraction analysis and scanning electron microscopy before and after Au(III) adsorption. To gain more detailed understanding of Au(III) adsorption at a molecular level, complexations of Au(III) with each amino acid component found in the peptides of HH was investigated. l -Cystine and l -cysteine were found to play a role in both the adsorption and reduction of Au(III). The mechanism of Au(III) adsorption and reduction on HH was investigated using proton nuclear magnetic resonance spectroscopy. The stepwise purification of three precious metals was also demonstrated: Pt(IV) and Pd(II) were successfully removed from HH by washing with acidic thiourea solution, while pure gold could be recovered by incineration. Thus, HH waste has shown potential as beneficial and efficient utilization on the separation and recovery of precious metals.